Using Performance on the Job to Inform Teacher Tenure Decisions - Goldhaber, Dan; Hansen, Michael (American Economic Review, 2010)
The notion that some high stakes need to be attached to direct measures of teachers’ class-room performance as a control for quality in the work force is an idea gaining traction in public education. One such proposal prescribes low-ering the barriers to entry into teaching while simultaneously being more selective about which teachers are retained when they become eligible for tenure (Robert Gordon, Thomas J. Kane, and Douglas O. Staiger 2006; Eric A. Hanushek 2009).